2011
DOI: 10.1042/bj20110739
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles of RNA helicase DDX3 and its interactions with eIF4E/PABP1 in stress granule assembly and stress response

Abstract: Upon environmental insults, SGs (stress granules) aid cell survival by serving as sites of translational silencing. RNA helicase DDX3 was reported to associate with SGs. However, its role in SG physiology remains undefined. We have demonstrated previously that DDX3 acts as an eIF4E (eukaryotic initiation factor 4E)-inhibitory protein to suppress translation. In the present study, we indentified the SG marker PABP1 [poly(A)-binding protein 1] as another direct interaction partner of DDX3. We established various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
192
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(207 citation statements)
references
References 33 publications
14
192
1
Order By: Relevance
“…Assembly occurs through aggregation of proteins such as TIA1 or G3BP, which can interact with mRNA leading to translationally stalled aggregates. The DDX3 RNA helicase can associate with stress granules and suppress translation through the inhibition of eIF4E (89). Additionally, molecules that inhibit eIF4A can promote stress granule formation independently of eIF2␣ (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Assembly occurs through aggregation of proteins such as TIA1 or G3BP, which can interact with mRNA leading to translationally stalled aggregates. The DDX3 RNA helicase can associate with stress granules and suppress translation through the inhibition of eIF4E (89). Additionally, molecules that inhibit eIF4A can promote stress granule formation independently of eIF2␣ (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…DDX3 has not only been implicated in contributing the innate immune response (48,51,62,79) but may also function in host cell translation initiation via an interaction with eukaryotic initiation factor 3 (eIF3) (38). Recent studies suggested that DDX3 contributes to HIV translation (39) and stress granule formation (64). eIF3 has been implicated to have a role in the unique mechanism of norovirus VPg-mediated translation initiation (11,12).…”
Section: Figmentioning
confidence: 99%
“…Like other RNP bodies, P granules are enriched in RNA-binding proteins, including PGL-1,-3 and the RNA helicases CGH-1, GLH-1-4, LAF-1, and VBH-1 (11). Members of the highly conserved DDX3 subfamily of DEAD-box RNA helicases, including human DDX3X, yeast Ded1p, and Drosophila Belle, have demonstrated roles in the assembly and remodeling of RNPs (12)(13)(14). Interestingly, many of these RNA helicases are predicted to be partially disordered, consistent with bioinformatic analysis, suggesting disordered motifs are common in RNP bodies (15).…”
mentioning
confidence: 99%